Resection of thyroid carcinoma infiltrating the trachea. Issue 3 (June 1978) - Ishihara, T; Kikuchi, K; Ikeda, T; Inoue, H; Fukai, S; Ito, K; Mimura, T
Abstract : We have treated surgically 11 patients with thyroid carcinoma that had infiltrated into the trachea. Three patients had primary tumours, and eight had recurrent tumours after previous operations. Sleeve resection of trachea was performed where thyroid carcinoma had proliferated; the trachea was reconstructed by end-to-end anastomosis. In two patients 10 rings of the trachea were resected. In three patients the anterior half of the cricoid cartilage was resected along with the cervical trachea. In one patient tracheoplasty was performed using partial extracorporeal circulation because severe tracheal stenosis prevented endotracheal intubation. Two of the 11 patients died from the surgery and one from disseminated metastases. One patient who had undergone tracheal resection for thyroid carcinoma three years and five months previously had a recurrence of the tumour in the trachea adjacent to the anastomosis, and a second tracheal resection was performed. In three patients postoperative laryngeal stenosis occurred. Five patients are alive and well two years and one month to four years and seven months after their operations. The histological pattern of the tumour was papillary adenocarcinoma in all 11 patients.